Online customer reviews about security and its impact on hostel prices: the importance of human rights - Cró, Susana (2021)
Based on a sample of consumer reviews of 637 hostels in 28 cities worldwide, with different levels of respect of human rights, we test if the security attribute has an impact on the price, depending on the level of respect for human rights. We chose a sample of countries with different levels of fulfilment of human rights by the fact that previous studies show that human rights violation has far more severe impacts on tourism activity than terrorist events. Results suggest that hostel guests are willing to pay a higher price in the countries with serious human rights violations, for a hostel room with higher levels of security. In the case of women and older guests, the premium they are willing to pay is higher. Results also show that as the institutionalised tourists,the backpackers are averse to risk and equally concerned about the risks of travel and destination.